Slur reclamation, irony, and resilience - Pavone, Luigi (Lodz papers in pragmatics, 2024)
The process of slur reclamation is a linguistic phenomenon whereby members of a targeted group begin to employ their own slur as a means of self-labelling, expressing pride, fostering camaraderie, and reversing the derogatory perspective of the slur. This action is designed to deprive racist and bigoted institutions of a means of perpetuating social power imbalances. Some authors posit that slur reclamation entails a shift in meaning. The ambiguity thesis (AT) can be developed in a variety of ways depending on the semantic level at which the derogatory content is situated. However, AT is subject to a number of criticisms, including what has been termed (AW). This paper seeks to elucidate the semantic mechanisms of slur reclamation without recourse to AT. To do this, an imperative account of slurs is adopted, which will be termed (WT). This account proposes that reclaimed uses of slurs are expressions of irony and resilience.